2023
DOI: 10.3390/ma16134716
|View full text |Cite
|
Sign up to set email alerts
|

Biochar from Grapevine Pruning Residues as an Efficient Adsorbent of Polyphenolic Compounds

Abstract: Agricultural waste, which is produced in large quantities annually, can be a threat to the environment. Biochar (BC) production represents a potential solution for reducing the amount of grapevine pruning residues and, accordingly, the impact on the environment and climate change. Biochar produced by the process of pyrolysis from grapevine pruning residues was investigated and characterized to be applied as an adsorbent of polyphenolic compounds with the aim of using the waste from viticultural production to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…Biochar adsorption capacity is a complex phenomenon affected by various factors, such as electrolyte content, temperature, pH, surfactant structure, pore volume, and the nature of the activated carbon used [ 39 , 40 ]. As previously reported, biochar from grapevine pruning residues is an efficient adsorbent of polyphenolic compounds [ 41 ].…”
Section: Introductionmentioning
confidence: 84%
“…Biochar adsorption capacity is a complex phenomenon affected by various factors, such as electrolyte content, temperature, pH, surfactant structure, pore volume, and the nature of the activated carbon used [ 39 , 40 ]. As previously reported, biochar from grapevine pruning residues is an efficient adsorbent of polyphenolic compounds [ 41 ].…”
Section: Introductionmentioning
confidence: 84%
“…In this study, the mentioned models were used to determine the adsorption process by which polyphenols from olive leaf extracts adsorb onto the BC from grapevine pruning residues. BC properties and adsorption capacity were described in our previous works [29,39]. Among all investigated compounds, hydroxytyrosol and the total amount of polyphenols fitted better in the Langmuir model, obtaining the R 2 closest to 1, suggesting the suitability of this model for the mentioned compounds' adsorption.…”
Section: Discussionmentioning
confidence: 55%
“…Those findings suggested that monolayer and heterolayer phenolic compounds may exist on the adsorbent surface due to the heterogeneity of the BC's surface [64]. In our previous work [29], BC from grapevine pruning residues was investigated as an adsorbent for polyphenols. In that paper, the standard of oleuropein, among others, was used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations